Dharibah and Tax Competition Policy as Considerations for Taxpayers in Choosing the Domicile of Motor Vehicles - Enceng Enceng; Damas Dwi Anggoro; Purwaningdyah Murti Wahyuni; M. Jeffri Arlinandes Chandra (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2023)
The study aims to develop an alternative policy model to address the tax competition phenomenon's impact on GDP in three provinces within the Jabodetabek region. The research employs a mixed methods approach. This methodology is chosen to address the problem formulations outlined in Chapter I. The first and second problem formulations are tackled through a qualitative approach, while the third problem formulation is addressed through a quantitative approach. Data collection involves preliminary studies and development using interview techniques, Focus Group Discussion (FGD), library studies, documentation, and questionnaires. Qualitative data analysis employs descriptive analysis, while quantitative analysis utilizes simple linear regression analysis processed with SPSS 21.0. The research findings reveal that: (1) the imposition of motor vehicle tax in Jakarta, Bogor, and Tangerang involves distinct policies, strategies, and evaluation methods; (2) inhibitory and driving factors contribute to the presence of tax competition in Jakarta and Bogor; (3) fiscal competition influences taxable decisions in selecting the domicile of motor vehicles. This is evident from the obtained R Square value of 0.095, indicating that tax competition influences the tax decision variable in choosing the motor vehicle domicile by 9.6%.